LKPD Berbasis Discovery-Learning Pada Materi Luas Permukaan dan Volume Prisma dan Limas - Satiti, Wisnu Siwi; Istiqomah, Ika Nur; Khotimah, Khusnul (Universitas KH. A. Wahab Hasbullah, 2022)
Mathematics learning has important and strategic roles in Indonesian education-system. One of mathematical subjects learnt at school is geometry. Many real-life contexts are related to concept of geometry, especially surface-area and volume. However, some previous studies show that many students have difficulties learning concepts of surface-area and volume of prisms and pyramids. This due to learning that only emphasizes on memorizing formulas makes the learning itself less meaningful for students, so students’ learning motivation is low. One alternative that can be done is the use of student worksheets (LKPD). This worksheet is based on a learning approach that facilitates students to build their understanding independently and present meaningful mathematical activities. Therefore, in this study, discovery-learning based worksheets were developed for surface-area and volume of prisms and pyramids. This study uses Research and Development method within ADDIE model. Result of this study shows that LKPD is valid. This is indicated by results of expert validation wich obtains 83.09% that meets valid criteria. Moreover, the assessment of experts on the aspect of